Enalapril Influence on Arterial Stiffness in Rheumatoid Arthritis Women: A Randomized Clinical Trial - Perez-Vazquez, Felipe; Bäck, Magnus; Chavarria-Avila, Efrain; Gomez-Bañuelos, Eduardo; Ramos-Becerra, Carlos G.; Pizano-Martínez, Óscar; Salazar-Páramo, Mario; Grover-Páez, Fernando; Nava-Zavala, Arnulfo H.; Cardona-Muñoz, Ernesto G.; Cardona-Müller, David; Duran-Barragán, Sergio; et al. (Frontiers in Medicine, 2020)
Introduction: Cardiovascular parameters disruption can be found in patients at early stages of rheumatoid arthritis (RA). The primary endpoint of this study was the reduction of arterial stiffness in RA patients without traditional cardiovascular risk factors or previous comorbidities, measured by cardio-ankle vascular index (CAVI) through the enalapril intervention. The secondary endpoints were the enalapril influence on carotid femoral pulse wave velocity (cfPWV), carotid intima media thickness (cIMT), carotid artery distensibility (cDistensibility), Young´s incremental elastic modulus (Einc)]. Materials and Methods: Fifty-three patients were enrolled in a clinical, randomized, closed-label trial. The subjects were randomly assigned into two groups: One receiving 5 mg of enalapril (27) or placebo (26), both twice a day. The drug was acquired at Victory Enterprises®. The placebo was kindly provided by the Universidad de Guadalajara (UdeG), as well as the blinding into two groups: A and B. Enalapril and placebo were packed into bottles without labeling. Clinical assessment included a structured questionnaire to gather demographic and clinical variables as well as determination of CAVI, cfPWV, cIMT, carotid artery distensibility and Einc. The whole set of evaluations were analyzed at the baseline and at the end of 12 weeks of intervention. Results: The CAVI measurement at baseline was 7.1±1.4 and increased up to 7.5±1.2 at the end of 12 weeks. Meanwhile, the enalapril group was as follows: 7.4±1.2 and at the of intervention, reduced to 7.1±0.9. A reduction in delta CAVI of 0.21 in the enalapril intervention group was found. In contrast, an increase of 0.39 was observed in the placebo group. The delta CAVI reduction was not influenced by age or peripheral systolic blood pressure (pSBP). Discussion: Enalapril seems to be effective in CAVI reduction in RA patients. The effect of enalapril intervention on arterial stiffness translated to the clinical context might be interpreted as a reduction of 6.4 years of arterial aging. Trial registration: The protocol was approved by the Institutional Review Board with the register CI-0117 from UdeG, and 0211/18 from Hospital Civil “Dr. Juan I. Menchaca”, Secretaría de Salud Jalisco: DGSP/DDI/D.INV.28/18 and retrospectively registered at ClinicalTrials.gov Protocol Registration and Results System: NCT03667131.